This is a simultaneous equation question.
Arrange both equations in line with their letters and numbers and then simplify them:
(3x-3y = 12) divide all terms by 3
(-8x+4y = -16) divide all terms by 4
This will give you:
x - y = 4
-2x+y = -4
Adding both equations together will give you:
-x = 0
So x = 0, substitute this value for x in the original equations to find the value of y:
x = 0 and y = -4
Note that -3*-4 = 12 and that +4*-4 = -16
28
(N/8)=(12/16) N= (12*8/16) N=6
12 divided by 3 equals 4. Then, 4 times 3 equals 12. Finally, 4 plus 12 equals 16.
12 = r/3 + 16
It does not.
Well, isn't that a happy little math problem! To find out what times 12 equals 16, we simply need to divide 16 by 12. The answer is 1.33, which means that 1.33 times 12 equals 16. Keep exploring those numbers and you'll create a beautiful mathematical landscape!
28
(N/8)=(12/16) N= (12*8/16) N=6
% rate = 12/16 * 100% = 75%
12 + 4 = 16
12 divided by 3 equals 4. Then, 4 times 3 equals 12. Finally, 4 plus 12 equals 16.
12 = r/3 + 16
28
192
It does not.
it equals 70
You plug in the values of x and y and solve 12x + 16y = ? 12(1) + 16(2) = 12 + 32 = 44